pH-responsive metal–organic framework–iron scaffolds for antibacterial and osteogenesis-promoting applications in diabetic infected bone defects - Yaxin Xue; Xinyu Ran; Danyang Zhao; Jian Wang; Hao Jiang; Chengji Wang; Wei Xu; Hao Lv; Zhencheng Yu; Zijing Du; Yi Cao; Dongmei Dong; et al. (Chemical Engineering Journal, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Deep learning and hyperspectral imaging for non-destructive amino acid detection in live carp fillets - Ying-jie Qi; Yi-Ming Cao; Yan Zhang; Qi Wang; Ran Zhao; Kai-Kuo Wang; Ying-Jie Chen; Xia-Jun Qi; Jiong-Tang Li (Food Research International, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Targeting ACSL4: A potential strategy to alleviate deoxynivalenol-mediated intestinal ferroptosis, oxidative stress, and immunosuppression in Channa argus - Yi-Ran Zhao; Tong-Hao Wang; Ze-Xin Zhao; Xiao-Tian Niu; Hong-Ming Lv; Yan-Bing Li; Yang Cao; Mu-Yang Li (Aquaculture, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

Comprehensive micellar / reversed-phase two-dimensional liquid chromatography for separation and identification of phenolic compounds in herbal tea by multivariate statistical analysis - Qian-Xue Shen; Yi-Wen Wu; Xin-Ran Ma; Jun Cao; Li-Hong Ye (Analytica Chimica Acta, 2026)

Superior degradation of endocrine disruptors over defective iron pyrites assisted by vacancy-induced disassociation of hydrogen peroxide - Han-Liang Fang; Yu-Hang Xu; Xiang-Min Jin; Hao-Ran Long; Wen-Ni Zhang; Han-Hui You; Zhou Zhong; Yi-Dong Hou; Hai-Lei Cao; Christopher Rensing; Jian Lü (Chemical Engineering Journal, 2025)

Tea saponin assisted micellar extraction combined with in-situ aqueous two phase enrichment of flavonoids and lactones from functional food - Si-Yi Liu; Xin-Ran Ma; Qian-Xue Shen; Huang-Fei Jin; Jun Cao (Food Research International, 2025)

Superhydrophilic hydrolyzed-TEOS modified rPET/PEG/SiO2 membranes for oil-in-water emulsion separation - Panchan Dansawad; Yi Fang; Lixia Cao; Haigang Gao; Cong Xue; Ruifeng Ran; Haofei Nie; Yanxiang Li; Wangliang Li (Journal of Environmental Chemical Engineering, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

The simulated in vitro infant gastrointestinal digestion of lipid droplets covered with milk fat globule membrane components: The role of interface layers - Zhixi Li; Yu Cao; Xiankang Fan; Hui Zhou; Pengjie Wang; Hao Zhang; Yi Wang; Ran Wang; Jie Luo (Food Research International, 2025)

Simultaneous extraction of flavonoids and saponins from functional food via basic deep eutectic solvent-assisted mechanochemical extraction - Yi-Wen Wu; Jie Zhang; Xin-Ran Ma; Jun Cao (Food Chemistry, 2025)

Suspended sediment (SPS) triggers nitrogen retention by altering microbial network stability and electron transport behavior during the aerobic-anoxic transition - Xiaoyan Liu; Tingting Pei; Guojia Xu; Tinglin Huang; Yaoguo Wu; Xiaowei Jin; Yi Cao; Ran Sun; Sihai Hu; Pathmalal M. Manage; Xiang Liu; Tao Liu; et al. (Journal of Environmental Management, 2025)

Enhanced degradation of exogenetic citrinin by glycosyltransferases in the oleaginous yeast Saitozyma podzolica zwy-2-3 - Qingzhuoma Yang; Shengtao Guo; Yulu Ran; Jie Zeng; Dairong Qiao; Hui Xu; Yi Cao (Bioresource Technology, 2024)

Vitamin consumption and the ontogenesis of cathepsins and antioxidant capacity in developing embryos of turbot, Scophthalmus maximus - Xuehong Tong; Sudan Ran; Yiqiu Feng; Linxi Cao; Yi Wang; Yueqin Wang; Yutian Zhuang; Xuexue Zhang (Aquaculture International, 2024)

Enhancement of lipid synthesis by the transcription factor Asg1 in Saitozyma podzolica zwy-2–3 under dissolved oxygen stress - Qingzhuoma Yang; Yulu Ran; Yihan Guo; Jie Zeng; Yao Song; Dairong Qiao; Hui Xu; Yi Cao (Bioresource Technology, 2024)

Polyamide and deep eutectic solvent assisted matrix solid-phase dispersion microextraction for strong hydrophobic compounds - Yi-Wen Wu; Xin-Ran Ma; Xin Peng; Xudong Cai; Jun Cao; Li-Hong Ye (Sustainable Chemistry and Pharmacy, 2024)

Nonlinear effects of agricultural drought on vegetation productivity in the Yellow River Basin, China - Yujie Ding; Lifeng Zhang; Yi He; Shengpeng Cao; Andrei Gusev; Yan Guo; Ling Ran; Xiao Wei; Filonchyk Mikalai (Science of The Total Environment, 2024)

Gigantic gastropods from the Middle Triassic Qingyan biota of Guizhou - Xin Sun; Li Tian; Chuan-Yuan Liu; Xiao He; Dao-Liang Chu; Xue Miao; Shi-Yan Zhang; Yi-Ran Cao; Pei-Shan Li; Jin-Nan Tong; Hai-Jun Song (Palaeoworld, 2024)

Freshwater microconchids from the Tanzhuang Formation (Middle-Late Triassic) in North China - Hao Yang; Yue Su; Hui-Jun Chen; Yi-Ran Cao; Meng-Yang Zhang; Rui Li; Dao-Liang Chu (Palaeoworld, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

Taming the anchor and conversion of polyselenides with a self-reinforcing host in lithium–selenium batteries - Hongyan Li; Wenda Dong; Yueqiang Cao; Tarek Barakat; Marvin Laboureur; Mao-Jin Ran; Zhi-Yi Hu; Hongxian Zhang; Cheng-Bin Jin; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2024)

Porous carbon prepared by thermal dissolution of coal and biomass for high-performance supercapacitors - Yi Liu; Wei-Dong Cao; Xing Fan; Ran-Ran Hou; Xiang Bai; Xiao-Yun Zhang; Yan Li; Guo-Ming Zhao; Peng Liang (Fuel, 2024)

Skillful prediction of boreal winter-spring seasonal precipitation in Southern China based on machine learning approach and dynamical ENSO prediction - Ting-wei Cao; Yi-ran Xu; Fei Zheng; Ruo-wen Yang (Theoretical and Applied Climatology, 2024)

Study on the mechanism of arsenic-induced renal injury based on SWATH proteomics technology - Xiaolu Chen; Xi Yan; Xiaoxiao Tang; Yi Wang; Xinglai Zhang; Xueshan Cao; Xiaoqian Ran; Guanwei Ma; Ting Hu; Ayesha Qureshi; Peng Luo; Liming Shen (Journal of Trace Elements in Medicine and Biology, 2024)

Spatiotemporal evolution of agricultural drought and its attribution under different climate zones and vegetation types in the Yellow River Basin of China - Yujie Ding; Lifeng Zhang; Yi He; Shengpeng Cao; Xiao Wei; Yan Guo; Ling Ran; Mikalai Filonchyk (Science of The Total Environment, 2024)

LSTM time series NDVI prediction method incorporating climate elements: A case study of Yellow River Basin, China - Yan Guo; Lifeng Zhang; Yi He; Shengpeng Cao; Hongzhe Li; Ling Ran; Yujie Ding; Mikalai Filonchyk (Journal of Hydrology, 2024)

Effects of arsenic exposure on trace element levels in the hippocampus and cortex of rats and their gender differences - Xi Yan; Jun Zhang; Junyu Li; Xinglai Zhang; Yi Wang; Xiaolu Chen; Peng Luo; Ting Hu; Xueshan Cao; Hongbin Zhuang; Xiaoxiao Tang; Fang Yao; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Spatial distribution and migration of lead and zinc and the influence of parent materials in typical paddy soils of Hunan Province, China - Yi-fan Xiang; Da-juan Wan; Chen-ran Wang; Jun-lin Huang; Xue-ying Cao; Jia-qi Chen; Ning-xiang Ouyang (Environmental Monitoring and Assessment, 2023)

Potential xylose transporters regulated by CreA improved lipid yield and furfural tolerance in oleaginous yeast Saitozyma podzolica zwy-2-3 - Yulu Ran; Qingzhuoma Yang; Jie Zeng; Fazhi Li; Yu Cao; Qingrui Xu; Dairong Qiao; Hui Xu; Yi Cao (Bioresource Technology, 2023)

Fog event is possibly a source rather than a sink of atmospheric nitrate aerosols: Insights from isotopic measurements in Nanjing, China - Hao-Ran Yu; Yan-Lin Zhang; Fang Cao; Zhu-Yu Zhao; Mei-Yi Fan; Xiao-Ying Yang (Applied Geochemistry, 2023)

Corrigendum to “Long-term environmental levels of microcystin-LR exposure induces colorectal chronic inflammation, fibrosis and barrier disruption via CSF1R/Rap1b signaling pathway” [J Hazard Mater 440 (2022) 129793] - Yue Yang; Hui Wang; Xiaoyan Wang; Ling Chen; Wenya Liu; Danping Cai; Shuxiang Deng; Hanyu Chu; Ying Liu; Xiangling Feng; Jihua Chen; Mengshi Chen; et al. (Journal of Hazardous Materials, 2023)

Matthew effect photoimmunotheranostics enabled by proton-driven nanoconverter - Jingjing Wang; Wei Zhang; Dachong Gu; Chunmei Chen; Wei Tang; Yi Ouyang; Xiaohong Liu; Shi-Yu Lu; Wei Zhang; Xingcai Zhang; Yulong Han; Jie Hu; et al. (Chemical Engineering Journal, 2023)

Influence of inertia on liquid splitting at fracture intersections - Zexiong Zhou; Zhibing Yang; Cao Luo; Song Xue; Chi Yao; Ran Hu; Yi-Feng Chen (Journal of Hydrology, 2023)

Repaired surface structural imperfection of tin Wide-Bandgap perovskite films for photovoltaic application - Tian-Yu Teng; Fan Hu; Yan-Hui Lou; Jun-Jie Cao; Chun-Hao Chen; Yi-Ran Shi; Kai-Li Wang; Jing Chen; Zhao-Kui Wang; Liang-Sheng Liao (Chemical Engineering Journal, 2023)

Categorizing objects from MEG signals using EEGNet - Ran Shi; Yanyu Zhao; Zhiyuan Cao; Chunyu Liu; Yi Kang; Jiacai Zhang (Cognitive Neurodynamics, 2022)

The effect of consecutive ambient air pollution on the hospital admission from chronic obstructive pulmonary disease in the Chengdu region, China - Yi Zhang; Ziyue Wang; Yu Cao; Lifu Zhang; Guan Wang; Fangjie Dong; Ren Deng; Baogen Guo; Li Zeng; Peng Wang; Ruimei Dai; Yu Ran; et al. (Air Quality, Atmosphere & Health, 2021)

KCNQ Channels in the Mesolimbic Reward Circuit Regulate Nociception in Chronic Pain in Mice - Hao-Ran Wang; Su-Wan Hu; Song Zhang; Yu Song; Xiao-Yi Wang; Lei Wang; Yang-Yang Li; Yu-Mei Yu; He Liu; Di Liu; Hai-Lei Ding; Jun-Li Cao (Neuroscience Bulletin, 2021)
Mesocorticolimbic dopaminergic (DA) neurons have been implicated in regulating nociception in chronic pain, yet the mechanisms are barely understood. Here, we found that chronic constructive injury (CCI) in mice increased the firing activity and decreased the KCNQ channel-mediated M-currents in ventral tegmental area (VTA) DA neurons projecting to the nucleus accumbens (NAc). Chemogenetic inhibition of the VTA-to-NAc DA neurons alleviated CCI-induced thermal nociception. Opposite changes in the firing activity and M-currents were recorded in VTA DA neurons projecting to the medial prefrontal cortex (mPFC) but did not affect nociception. In addition, intra-VTA injection of retigabine, a KCNQ opener, while reversing the changes of the VTA-to-NAc DA neurons, alleviated CCI-induced nociception, and this was abolished by injecting exogenous BDNF into the NAc. Taken together, these findings highlight a vital role of KCNQ channel-mediated modulation of mesolimbic DA activity in regulating thermal nociception in the chronic pain state.

Aberration of Serum and Tissue N-Glycans in Mouse β1,4-GalT1 Y286L Mutant Variants - Ran Cao; Tian-Chan Zhang; Ya-Ran Chen; Cui Cao; Huan Chen; Yi-Fan Huang; Morihisa Fujita; Li Liu; Josef Voglmeir (Glycoconjugate Journal, 2020)

Recovery of unstable digestion of vegetable waste by adding trace elements using the bicarbonate alkalinity to total alkalinity ratio as an early warning indicator - Dong Li; Juan Sun; Qin Cao; Yichao Chen; Xiaofeng Liu; Yi Ran (Biodegradation, 2019)

Improving Cu(II) sorption by biochar via pyrolyzation under CO2: the importance of inherent inorganic species - Ran Wen; Bo Yuan; Yang Wang; Weimin Cao; Yuan Liu; Yi Jia; Qiang Liu (Environmental Science and Pollution Research, 2018)

L1CAM drives oncogenicity in esophageal squamous cell carcinoma by stimulation of ezrin transcription - Jin-Cheng Guo; Yang-Min Xie; Li-Qiang Ran; Hui-Hui Cao; Chun Sun; Jian-Yi Wu; Zhi-Yong Wu; Lian-Di Liao; Wei-Jiang Zhao; Wang-Kai Fang; En-Min Li; Li-Yan Xu; et al. (Journal of Molecular Medicine, 2017)